Negative Body Image Is Not Related to Spontaneous Body-Scaled Motoric Behavior in Undergraduate Women - Glashouwer, Klaske A.; Meulman, Charlotte; de Jong, Peter J. (Frontiers in Psychology, 2019)
Body image disturbance is a core characteristic of anorexia nervosa which might be grounded in distortions in schematic body representations. In line with this, several studies showed that when walking through door-like apertures of different widths individuals with anorexia nervosa move as if their bodies are larger than they actually are. They turn their body at a higher aperture/shoulder width ratio than healthy individuals. We examined whether oversized body-scaled motoric behaviors may not be restricted to anorexia nervosa but concern a general feature of negative body image attitudes. Therefore, we investigated the relation between negative body image as assessed with shape and weight concerns subscales of the Eating Disorder Examination Questionnaire and aperture/shoulder width turning ratios in women with a healthy weight (N = 62). We found that a more negative body image was unrelated to higher aperture/shoulder width turning ratios. Bayes analysis provided moderate evidence for the null hypothesis that spontaneous body-scaled motoric behaviors are not involved in negative body image. Future studies should disentangle whether being underweight per se is related to distinctive spontaneous body-scaled motoric behaviors or whether an ‘oversized’ body schema is a unique characteristic of anorexia nervosa, potentially contributing to the persistence of this disorder.